Peculiarities of Si-Ge whisker growing by CTR method - Druzhinin, A.A.; Ostrovskii, I.P.; Khoverko, Yu.M.; Gij, Ya.V. (Functional Materials, 2005)
Growth peculiarities of doped Si₁₋ₓGeₓ (х = 0.01-0.05) solid solution whiskers of 1 to 100 µm in diameter in closed bromide system by chemical transport reactions method have been investigated. А dimensional dependence of specific resistance at 300 К has been revealed. The Si₁₋ₓGeₓ (х = 0.05) whiskers of 30 to 70 µm in diameter with dopant concentration in the vicinity of metal-insulator transition were obtained. Substantial changes of the specific resistance and gauge factor of the crystals depending on their diameters has been observed in temperature range 4.2-50 К.